2001
DOI: 10.1021/ac0011383
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Five β-Lactam Antibiotics in Bovine Milk Using Liquid Chromatography Coupled with Electrospray Ionization Tandem Mass Spectrometry

Abstract: A multiresidue method for the detection of five important beta-lactam antibiotics (amoxicillin, ampicillin, cloxacillin, oxacillin, penicillin G) in fresh milk is presented that allows quantitation of the analytes well below established legislative limits. The method avoids the use of acid during the extraction procedure and entails a cleanup step over a C18 cartridge. The analytes are separated and detected by liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) using a stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 23 publications
0
53
0
1
Order By: Relevance
“…We have set the cone voltage from 20 to 80 V at an interval of 20 V, and the maximum structural information was obtained at 60 V for all the analytes except for penilloic acid and penicilloaldehyde, which were obtained at 80 V as shown in Table 1. It has been reported that fragmental ions of PEN G were m/z 160 and 176 in the positive ion mode (Riediker and Stadler, 2001), and m/z 192 and 289 in the negative mode (Becker et al, 2004) using LC-ESI/MS/MS. In this study, fragmental ions were found to be m/z 192 and 289 for PEN G, the same as that reported using LC-ESI/MS (Straub and Voyksner, 1993).…”
Section: Qualification and Quantificationmentioning
confidence: 99%
“…We have set the cone voltage from 20 to 80 V at an interval of 20 V, and the maximum structural information was obtained at 60 V for all the analytes except for penilloic acid and penicilloaldehyde, which were obtained at 80 V as shown in Table 1. It has been reported that fragmental ions of PEN G were m/z 160 and 176 in the positive ion mode (Riediker and Stadler, 2001), and m/z 192 and 289 in the negative mode (Becker et al, 2004) using LC-ESI/MS/MS. In this study, fragmental ions were found to be m/z 192 and 289 for PEN G, the same as that reported using LC-ESI/MS (Straub and Voyksner, 1993).…”
Section: Qualification and Quantificationmentioning
confidence: 99%
“…Several methods have been reported for the simultaneous determination of veterinary drugs in muscle. [3][4][5][6][7][8][9][10] Most of these methods were developed with the intention of determining analogous compounds, [5][6][7][8][9][10][11][12][13][14] and there are scarcely any reports on methods developed with the intention of simultaneous determination of compounds belonging to various classes. Liquid chromatography coupled with electrospray ionization tandem mass spectrometry (LC/MS/MS) affords a highly specific method of determining various compounds by providing structural information.…”
mentioning
confidence: 99%
“…There is a constant requirement for accurate, sensitive and selective analytical methods for monitoring nafcillin antibiotic residues to guarantee the safety of food. Usually, the complexity of food matrices and contaminants presented in food at low concentration (ng g -1 to ȝg g -1 ) levels require analysis performance only after some clean-up and preconcentration steps [2][3][4] , and thus there is a considerable interest in developing new specific and selective methods for extracting and isolating components from complex food matrices. For this purpose, the solid phase extraction (SPE) technique is the most widely used for sample pre-treatment method due to its advantages such as convenience, low cost, timing saving and simplicity.…”
Section: Introductionmentioning
confidence: 99%